Existência e linguagem: o problema do sentido na filosofia da história de Paul Ricoeur - Breno Mendes (2019)
The problem of sense in Paul Ricoeur's philosophy of history is the focus of this research. The interpretation is developed from the hypothesis in which would exist a dialectic between existence and language in the constitution of sense and meaning. The strategy chosen in the investigation was the reading of works that cover a significant part of Ricoeur's philosophical path, demonstrating how he articulated a philosophy of existence with a philosophy of language. Throughout the thesis, our purpose is to understand Ricoeur's comprehension of the dialectic between ontology and epistemology in philosophy of history. Finally, in our conclusion, we will essay the possibility that difficult forgiveness will be understood as a way to believe in history today.